Effect of neurokinin B and dynorphin A on kisspeptin-10 secretion from the anterior pituitary cells of pubescent ewes in vitro - Szysiak Natalia; Kosior-Korzecka Urszula; Greguła-Kania Monika; Patkowski Krzysztof; Fila Mateusz; Junkuszew Andrzej (Journal of Veterinary Research)
Neurokinin B (NKB), dynorphin A (Dyn A) and kisspeptin (KiSS) are key agents that participate in the neuroendocrine regulation of the development and functioning of the reproductive system. While the role of KiSS is better understood, the functions of NKB and Dyn A at the pituitary level have not been elucidated. The objective of our study was to analyse their direct effect on kisspeptin-10 (KiSS-10) secretion by anterior pituitary cells isolated from pubescent ewes.